2008
DOI: 10.1155/2008/868369
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preoperative Endoscopic Ultrasound on the Surgical Management of Pancreatic Neuroendocrine Tumours

Abstract: GS Sandha. The impact of preoperative endoscopic ultrasound on the surgical management of pancreatic neuroendocrine tumours. Can J Gastroenterol 2008;22(10):817-820.BACKGROUND: Endoscopic ultrasound (EUS) is accurate in diagnosing pancreatic neuroendocrine tumours (PNETs), but its impact on surgical management is unclear. OBJECTIVE: To determine whether preoperative EUS findings altered the decision for, and extent of, surgery in patients with PNETs. METHODS: A retrospective review of patients referred for EUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Since the introduction of the 64-detector CT, the detection rate has increased significantly to 89%. Recent studies 21,24 (Table 3) have reported similar improved CT detection rates for PNETs. Alsohaibani et al 24 reported a CT detection rate of 77% in their 2008 series.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Since the introduction of the 64-detector CT, the detection rate has increased significantly to 89%. Recent studies 21,24 (Table 3) have reported similar improved CT detection rates for PNETs. Alsohaibani et al 24 reported a CT detection rate of 77% in their 2008 series.…”
Section: Discussionmentioning
confidence: 74%
“…A number of older studies have also reported the superiority of EUS over CT for detecting PNETs (Table 3). These studies are heterogeneous in design, many involved very small number of patients, 16,21,22,[24][25][26] some did not uniformly use surgical pathology as a criterion standard for PNET diagnosis, 17,21,24 and others combined PNETs and extrapancreatic tumors in their analysis. 16,27 Other studies that have reported CT and EUS detection rates were not designed to compare the two modalities.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier works both sensitivity and precision were low, with a specificity of 100% (6); however, they gradually increased, and sensitivity reached about 90% (94% in the most extensive series in the literature) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (Table II).…”
Section: Discussionmentioning
confidence: 86%
“…In a large series, EUS correctly localized PNET in 93% of cases [30]. Others have reported detection of PNET by EUS to be in the range 82-100% [9,16,18,[31][32][33][34][35]. In a case-control study including 36 patients who underwent surgical exploration without undergoing an EUS, EUS was found to be highly accurate and cost-effective when used early in the preoperative location strategy.…”
Section: Discussionmentioning
confidence: 87%